CRITICAL PLANES CRITERIA APPLIED TO GEAR TEETH: WHICH ONE IS THE MOST APPROPRIATE TO CHARACTERIZE CRACK PROPAGATION? - CONCLI, FRANCO; Maccioni, Lorenzo (WIT Transactions on Engineering Sciences, 2021)
Tooth root bending fatigue is the most dangerous failure mode in gears. Indeed, it starts from the nucleation of a crack within the tooth root fillet region and the subsequent propagation up to the complete breakage of the tooth. To investigate this phenomenon, Single Tooth Bending Fatigue (STBF) tests are largely diffused. In these tests, an alternating bending stress at the tooth root is induced by the application of a pulsing force to the gear flank. In addition, this loading condition can be modelled through Finite Elements (FE) to study the stress state in the affected area. However, the application of strength criteria such as von Mises’ can provide the equivalent stresses when the applied force reaches its maximum value but does not provide any insight in terms of fatigue behaviour. Nevertheless, the crack propagation can be investigated by analysing the results of FE analyses (which model the entire load cycle) through fatigue criteria based, for instance, on the critical plane concept. Previous studies conducted by the authors have shown that the different fatigue criteria (to study the tooth bending failure) lead to very different results. Therefore, the objective of the present paper is to compare the results of analyses carried out with different fatigue criteria based on critical plane, i.e. Findley, Matake, McDiarmid, Papadopoulos, and Susmel, with experimental outcomes, i.e. STBF tests on an aeronautical gears, to determine the most appropriate fatigue criterion to characterize the fatigue behaviour of these mechanical components. Results reveal that all fatigue criteria lead to consistent results when the target is to identify the most critical point. However, the Findley and Papadopulus criteria are found to be the most accurate for what concerns the evaluation of the damage. Among the others, Susmel turns out to be the most conservative criterion while the Findley criterion is the only one capable of identifying with good accuracy the direction of crack propagation.